The level of effectiveness of online video games in connecting people / Adam Haziq Aznan, Irvina Joan Jeffry Douglas and Nurlisa Mohamad Ridzwan - Aznan, Adam Haziq; Jeffry Douglas, Irvina Joan; Mohamad Ridzwan, Nurlisa (Faculty of Communication & Media Studies, 2023)
This is a study that examines on video games and interaction of human beings. The trend that the researchers choose to examine is regarding the level of effectiveness of online video games in connecting people. Social networking sites are chosen as they bring many benefits to the users. The creation of technology that we have today is so accessible and advanced. It has the potential of becoming a routine component of networking and connecting people like social media. This study used social capital theory as foundations theories for model development. The minimum sample size was determined through Rao soft Calculator software. The study involved 422 respondents, selected through a cluster sampling technique involving three main ethnics in Malaysia. A cross sectional survey and structured questionnaire were used for data collection. All variables were measured through scales previously used by other researchers. SPSSS ver. 20 software was used in the analysis. Results of the SPSS indicated that the level acceptance of video games in connecting people is high (m=3.52).